The Psychological Effects of Videogames on the Cognitive Development in Children - Samia Mustafa,; Dr. Abdur Rashid*,; Maria Rafique, (Al-Qanṭara, 2023)
This cross-sectional study investigated the impact of video games on children's cognitive development and the risk of addiction. Data from 100 respondents in Rawalpindi were analyzed using SPSS software. The study found a significant negative association between video game use and cognitive development in children, indicating detrimental effects on attention, memory, problem-solving, and executive functions. It also revealed a positive association between video game use and addiction, highlighting the increased likelihood of developing addictive behaviors related to gaming. These findings emphasize the need for limits on children's video game exposure and a balanced approach to gaming and other activities supporting cognitive development. Parents, educators, and policymakers should be aware of the risks associated with excessive video game use and implement measures to monitor and regulate children's gaming habits. The study acknowledges limitations, including the cross-sectional design's inability to establish causality and the potential impact of the sample size and selection method on generalizability. Future research should employ longitudinal designs and diverse samples to enhance the findings' applicability. Overall, this study contributes valuable insights into the negative impact of video games on children's cognitive development and the importance of interventions to mitigate these effects and promote healthy cognitive development Keywords: Video games, Cognitive development, Addiction, Children, Psychological effects, Depression